Friction between different wire bracket combinations in artificial saliva: an in vitro evaluation (Journal of Applied Oral Science, 2011)
OBJECTIVE: The objective this work was to assess the friction coefficient between brackets and wires of different materials under conditions simulating the oral environment. MATERIAL AND METHODS: Stainless steel (SS) and titanium-molybdenum alloy (TMA) wires of 0.019x0.025-in diameter (American Orthodontics) and polycarbonate bracket (American Orthodontics), ceramic bracket (American Orthodontics), and metal bracket (3M Unitek) with slots of 0.022x0.030-in were used. The friction coefficient was assessed by means of mechanical traction with the system immersed in artificial saliva. The mean roughness of both wire surface and bracket slots was evaluated by using a surface profilometer. RESULTS: The system using TMA wire and polycarbonate bracket had the highest roughness (p